Dopant profile control of epitaxial emitter for silicon solar cells by low temperature epitaxy - Lai, Donny (2017)
We report an alternative approach to grow phosphorus-doped epitaxial silicon emitter by rapid thermal chemical vapor deposition at low temperature (T ≥ 700 °C). A power conversion efficiency (PCE) of (6.6 ± 0.3)% and a pseudo PCE of (10.2 ± 0.2)% has been achieved for the solar cell with epi-emitter grown at 700 °C, in the absence of surface texturization, antireflective coating, and back surface field enhancement, without considering front contact shading. Secondary ion mass spectroscopy revealed that lower temperature silicon epitaxy yields a more abrupt p-n junction, suggesting potential applications for radial p-n junction wire array solar cells.